Increased bone formation in a rabbit long-bone defect model after single local and single systemic application of erythropoietin. (3rd July 2016) - Omlor, Georg W; Kleinschmidt, Kerstin; Gantz, Simone; Speicher, Anja; Guehring, Thorsten; Richter, Wiltrud
Abstract : Background and purpose — Delayed bone healing with non-union is a common problem. Further options to increase bone healing together with surgery are needed. We therefore evaluated a 1-dose single application of erythropoietin (EPO), applied either locally to the defect or systemically during surgery, in a critical-size rabbit long-bone defect. Material and methods — 19 New Zealand White rabbits received a 15-mm defect in the radius diaphysis. An absorbable gelatin sponge was soaked with saline (control group and systemic treatment group) or EPO (local treatment group) and implanted into the gap. The systemic treatment group received EPO subcutaneously. In vivo micro-CT analysis was performed 4, 8, and 12 weeks postoperatively. Vascularization was evaluated histologically. Results — Semiquantitative histomorphometric and radiological evaluation showed increased bone formation (2.3- to 2.5-fold) in both treatment groups after 12 weeks compared to the controls. Quantitative determination of bone volume and tissue volume showed superior bone healing after EPO treatment at all follow-up time points, with the highest values after 12 weeks in locally treated animals (3.0- to 3.4-fold). More vascularization was found in both EPO treatment groups. Interpretation — Initial single dosing with EPO was sufficient to increase bone healing substantially after 12 weeks of follow-up. Local application inside the defect was most effective, and it can be administered directly during surgery. Apart from effects on ossification, systemic and local EPO treatment leads to increased callus vascularization.